Optimalisasi Peningkatan Pengetahuan Tentang Kesehatan Remaja Melalui Kegiatan Edukasi Pada Siswa SMP Negeri 32 Maluku Tengah - Putri Azizah; Fadli Afriandi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Adolescents represent the largest demographic group in Indonesia and are in a transitional developmental phase that makes them vulnerable to various health issues, including reproductive health and anemia. The lack of knowledge among adolescents about reproductive health and the high prevalence of anemia among adolescent girls have become serious concerns. According to data from the Indonesian Ministry of Health, the prevalence of anemia among adolescents aged 15-24 years reaches 32%, with a higher proportion among girls. To address this issue, a community service program was conducted in Negeri Saleman to enhance students' knowledge of reproductive health and anemia prevention at SMP Negeri 32 Central Maluku. This activity took place on August 12, 2024, involving 77 participants. The intervention included education on the importance of reproductive health, anemia prevention, and ways to address health issues among adolescents. This initiative proved effective in increasing adolescents' knowledge and understanding, as well as improving reproductive health indicators and preventing anemia among adolescent girls. The program had a positive impact by raising awareness and providing valuable knowledge that benefits adolescent health in the future.